Faktor-Faktor yang Mempengaruhi Penawaran Biji Kakao Non Fermentasi di Desa Lembah Subur Kecamatan Dangia Kabupaten Kolaka Timur - Wahyunis, Wahyunis; Rosmawaty, Rosmawaty; Indarsyih, Yusna (Department of Agribusiness, Halu Oleo University, 2018)
The purpose of this study is to analyze the factors that affect the supply of non fermented cocoa beans have been in Lembah Subur Village, Dangia Sub-District, East Kolaka District. Determination of sample is done by Simple Random Sampling that is by taking 10% from total population (455 people) so that the number of sample is 46 people. The data analysis used is multiple linear regression analysis. The result of the research shows that based on the result of forecasting with least square method variable of land area have real effect to the result of cocoa sale in Lembah Subur Village. While the selling price of non fermented cocoa beans, production cost, age of cocoa plants, farmer age and experience of farming did not significantly affect the sales of non fermented cocoa beans in Lembah Subur village, Dangia sub-district, East Kolaka regency